2005
DOI: 10.1063/1.2142289
|View full text |Cite
|
Sign up to set email alerts
|

High carrier mobility in low band gap polymer-based field-effect transistors

Abstract: A conjugated polymer with a low band gap of 1.21 eV, i.e., absorbing infrared light, is demonstrated as active material in field-effect transistors (FETs). The material consists of alternating fluorene units and low band gap segments with electron donor-acceptor-donor units composed of two electron-donating thiophene rings attached on both sides of a thiadiazolo-quinoxaline electron-acceptor group. The polymer is solution-processable and air-stable; the resulting FETs exhibit typical p-channel characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
41
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 20 publications
1
41
0
Order By: Relevance
“…We demonstrate for the first time that BBT-based polymers are promising materials for use in bulk-heterojunction solar cells. Keywords: bis-benzothiadiazole · carbazole · donor-acceptor systems · polymers · solar cells stronger electron acceptors, for example, thienoA C H T U N G T R E N N U N G [3,4-b]pyrazine, [32,33] [1,2,5]thiadiazoloA C H T U N G T R E N N U N G [3,4g]quinoxaline, [34] and pyrazinoA C H T U N G T R E N N U N G [2,3g]quinoxaline, [27] which leads to relatively lower band gap polymers than benzothiadiazole-based D-A polymers. However, no improvement of the overall PCEs has been achieved in comparison to the devices from benzothiadiazole-based D-A polymers/PCBM.…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrate for the first time that BBT-based polymers are promising materials for use in bulk-heterojunction solar cells. Keywords: bis-benzothiadiazole · carbazole · donor-acceptor systems · polymers · solar cells stronger electron acceptors, for example, thienoA C H T U N G T R E N N U N G [3,4-b]pyrazine, [32,33] [1,2,5]thiadiazoloA C H T U N G T R E N N U N G [3,4g]quinoxaline, [34] and pyrazinoA C H T U N G T R E N N U N G [2,3g]quinoxaline, [27] which leads to relatively lower band gap polymers than benzothiadiazole-based D-A polymers. However, no improvement of the overall PCEs has been achieved in comparison to the devices from benzothiadiazole-based D-A polymers/PCBM.…”
Section: Introductionmentioning
confidence: 99%
“…Donor–acceptor conjugated polymer systems have emerged as promising candidates for flexible organic electronic devices since their electronic and optoelectronic properties could be efficiently described by intramolecular charge transfer (ICT) 1–6. The studied polymer systems included alternating or random copolymers, polymer blends, and multilayer in the application areas of polymer light‐emitting diodes,7–15 field‐effect transistors (FET),6, 16–21 electrochromic devices,22 and photovoltaic devices 23–31…”
Section: Introductionmentioning
confidence: 99%
“…FET‐based thiophene‐ or fluorene‐based donor–acceptor conjugated polymers have been explored by several groups and us recently 6, 16–19. The studied thiophene‐acceptor conjugated polymers either exhibit p ‐type or ambipolar carrier mobility, including poly(thiophene‐thienopyrazine‐thiophene),6 poly(thiophene‐thiazole),17 poly(thiophene‐pyridazine‐thiophene),18 poly(thiophene‐ alt ‐thiadiazole),20 and poly(thiophene‐ alt ‐quinoxaline) 19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them are donor-acceptor pairs mediated by salt bridges [13], thienopyrazine-based copolymers [14], n-type conjugated polymers based on electron-deficient tetraazabenzodifluoranthene diimide [15][16][17][18], etc. Such conjugated polymer semiconductors with electron donor-acceptor transfer have become of growing interest for organic electronic applications [19][20][21][22], such as photovoltaic cells [23][24][25], light emitting diodes (LEDs) [26][27][28][29], and field-effect transistors [30][31][32][33]. During the past decade more evidence for the electron transport in DNA [34][35][36][37][38] (see review [39]) has also been reported.…”
Section: Introductionmentioning
confidence: 99%